2011 Agricultural Census In Serbia – Strategic tool for boosting rural development programs - Turtoi, Crina; Marković, Dragana; Gavrilescu, Camelia (Economics of Agriculture, 2010)
The elaboration of strategic programs for the development of rural areas requires rigorous and comprehensive analysis accompanied by an increased demand for data, as an inherent support for this work. The objective of this paper is to bring into the attention of the academic community the particularities and the main concerns regarding the implementation of the 2011 Agricultural Census in the Republic of Serbia, as an answer to the endeavors for satisfying the data demands of the bodies involved in the use of agricultural statistics for analyzing the emerging issues in agriculture, especially those concerning environment and rural development. On the road of accession to European Union the role of agricultural statistics in the frame of the European Statistical System is a prerequisite for comparable information, indispensable to the implementation of the Common Agricultural Policy. Main methodological and organizational aspects regarding the next agricultural census are the main topics of this paper.